Potency and Development Strategy of Sungai Bersejarah Mangrove Ecotourism, Siak Regency - EFFENDI, Irwan; NURSYIRWANI, Nursyirwani; PANJAITAN, Warren Pangihutan; YOSWATY, Dessy; GHALIB, Musrifin; RAZMAN, Muhammad Rizal; ANDRIZAL, Andrizal (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
Ecotourism, also called sustainable tourism, is a trendy mode of tourism today. Sungai Bersejarah mangrove ecosystem is one of the tourist attractions in Siak, Indonesia. This research was carried out from October 2020 to January 2021, aimed to determine the profile, potential and formulated a development strategy the area as an ecotourism destination. Data were collected from observations in the field, interviews with tourists and other tourism stakeholders. The data obtained were analyzed descriptively. The location can be reached by 4-wheeled vehicles, good road conditions and is 200 km to the capital of Riau Province (Pekanbaru). Existing facilities include parking areas, gates, tracking, seating, photo spots, huts, mangrove nurseries, and relaxing pier. The mangrove species found are Avicennia marina, Sonneratia alba, Rhizophora apiculata, Excoearia agallocha, Xylocarpus granatum, Bruguiera gymnorrhiza, Rhizophora stylosa and Nypa fruticans . The mangrove density is 2,500 tree/ha and dominated by R. stylosa, X. granatum and E. agallocha . Animals in this location include birds, reptiles, mammals, amphibians, insects, decapoda, gastropods and fishes. The tourism suitability index (TSI) of this area is 74.53%. The SWOT (strength, weakness, opportunity and threat) analysis recommends a set of strategy, namely fulfilling facilities, involvement of the surrounding community, human resources development and promotion.